Unprecedented ferrocene-quinoline conjugates: facile proton conduction via 1D helical water chains and a selective chemosensor for Zn(II) ions in water - Ponniah, Joseph S.; Barik, Subrat Kumar; Borthakur, Rosmita; Thakur, Arunabha; Garai, Bikash; Janaa, Sourita; Ghosh, Sundargopal (RSC Advances, 2015)
Two novel ferrocene-quinoline derivatives 3 (C22H19O2N3Fe) and 4 (C34H28O4N6Fe) have been synthesized and structurally characterized. Compound 3 exhibits good proton conductivity through 1D helical water chains. In addition, both compounds 3 and 4 selectively detect Zn2+ ions in water with a detection limit of 2 ppb through multiple channels.

Template -free assembly in living bacterial suspension under an external electric field - Samantaray, Kunal; Bhol, Prachi; Sahoo, Bhaban; Barik, Subrat Kumar; Jathavedan, Kiran; Sahu, Bikash Ranjan; Bikash Ranjan; Suar, Mrutyunjay; Bhat, Suresh K.; Mohanty, Priti Sunda (ACS Omega, 2017)
Although template-assisted self-assembly methods are very popular in materials and biological systems, they have certain limitations such as lack of tunability and switchable functionality because of the irreversible association of cells and their matrix components. With an aim to achieve more tunability, we have made an attempt to investigate the self-assembly behavior of rod-shaped living bacteria subjected to an external alternating electric field using confocal microscopy. We demonstrate that rod-shaped living bacteria dispersed in a low salinity aqueous medium form different types of reversible freely suspended structures when subjected to an external alternating electric field. At low field strength, an oriented phase is observed where individual bacterium orients with its major axis aligned along the field direction. At intermediate field strength, bacteria align in the form of one-dimensional (1D) chains that lie along the field direction. Further, at high field strength, more bacteria associate with these 1D chains laterally to form a two-dimensional (2D) array. At higher bacterial concentration, these field-induced 2D arrays extend to form three-dimensional columnar structures. These results are discussed in the context of previously reported studies on bacterial self-assembly.
Keywords: Bacteria; Electric Properties; Self- Assembly